USING OF NATURAL ADSORBENTS IN PROCESSES OF PETROLEUM PRODUCTS’ CLEARING - Ivanov, Sergey V.; Kustovska, Antonina D.; Nedaiborshch, Sergey D.; Kharchenko Оlena V. (Proceedings of National Aviation University (archive), 2008)
Questions, that concern the ability to use natural sorbent – poligorskite of Cherkassy deposit – in processes of petroleum products’ clearing, are considered. The influence of different methods of samples’ preparation on efficiency of adsorption clearing of furnace fuel, is researched. Comparative characteristic of adsorbent’s selectivity toward different pollutions was made. High effectiveness of using of natural poligorskite for extraction of acidic pollutions from petroleum products was showed.